2021
DOI: 10.3390/curroncol28010077
|View full text |Cite
|
Sign up to set email alerts
|

How Canadian Oncologists Use Oncotype DX for Treatment of Breast Cancer Patients

Abstract: Background: The literature suggests that medical oncologists differ on how they use the Oncotype DX (ODX) genomic assay for making decisions about systemic therapy in breast cancer patients. Given the emergence of data supporting the use of genomic profiling for the prognosis and predicting benefit of chemotherapy, we surveyed medical oncologists in Canada to assess their usage and perception of the ODX assay. Methods: A 34-item survey was distributed to Canadian medical oncologists via the Canadian Associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The ODX report also includes an ER (as well as progesterone receptor [PR] and HER2) gene score as an external validation of the ER status of the case under analysis. The ODX RS has been validated in large retrospective and prospective clinical trials [ 16 , 17 ] and has been incorporated as an essential element in adjuvant therapy decision-making for this breast cancer subtype in jurisdictions where it is funded [ 18 , 19 ]. A RS of >25 predicts significant benefit from the addition of chemotherapy to ET for the postmenopausal patient population.…”
Section: Introductionmentioning
confidence: 99%
“…The ODX report also includes an ER (as well as progesterone receptor [PR] and HER2) gene score as an external validation of the ER status of the case under analysis. The ODX RS has been validated in large retrospective and prospective clinical trials [ 16 , 17 ] and has been incorporated as an essential element in adjuvant therapy decision-making for this breast cancer subtype in jurisdictions where it is funded [ 18 , 19 ]. A RS of >25 predicts significant benefit from the addition of chemotherapy to ET for the postmenopausal patient population.…”
Section: Introductionmentioning
confidence: 99%
“…This score helps decide the benefit of chemotherapy for hormone receptor-positive, HER2-negative breast cancer patients [ 20 ]. Oncotype DX has revolutionized personalized breast cancer treatment, enabling clinicians to tailor therapies based on individual genetic profiles, thereby optimizing outcomes and avoiding overtreatment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several previous studies have found that the 21-gene RS could also predict the survival of N1 patients and have an impact on treatment decisions ( 8 , 10 13 ). In Canada, the 21-gene RS has been publicly funded for patients with N0 and ER+/HER2- BC for several years, whereas the coverage of RS testing for N+ patients has been very limited ( 14 ). Given emerging data on the role of RS and the recent discrepant treatment in these patients, this study aimed to clarify the practice patterns and the potential benefit of 21-gene testing in BC patients with ER+/HER2− and one to three LNs.…”
Section: Introductionmentioning
confidence: 99%